ENTREPRENEURIAL COMPONENT IN THE PROFESSIONAL TRAINING OF RENEWABLE ENERGY SPECIALISTS: FOREIGN AND DOMESTIC EXPERIENCE (Innovative professional education, 2025)
Based on the analysis of the entrepreneurial component’s content, the theoretical and methodological foundations for its formation in the professional training of renewable energy specialists have been determined within the context of domestic and European educational spaces. The research investigates the experience of selected European countries and the domestic vocational (professional-technical) education system regarding the integration of entrepreneurial skills into technical training for renewable energy source specialists. It is demonstrated that entrepreneurial competence serves as a strategic instrument for overcoming human resource challenges and ensuring innovative development in the renewable energy sector.
Keywords: renewable energy sources, entrepreneurial competence, professional education, educational institutions, educational program